The Relationship Between Religion and Science: Perspectives from Islamic and Western Philosophy - Maspuroh Maspuroh; Siti Latifah; Siti Mariam; Fauzan Abdul Aziz (Al-Falsafah: Jurnal Pemikiran dan Filsafat Islam, 2026)
This article comparatively analyzes the relationship between religion and science through the lens of Islamic philosophy and Western philosophy. Science and religion, although often considered to have separate domains (empirical-rational versus revelation-belief), both strive to achieve truth. Historically, Islamic philosophy has tended to favor an integration-complementary model, viewing the universe and revelation as "ayat-ayat Allah" (signs of God) that complement each other in the search for ilm (knowledge). The sources of knowledge are not only reason (akal) and senses, but also revelation (the Qur'an and Sunnah), resulting in a holistic-integralistic view. Conversely, modern Western philosophy, rooted in the Enlightenment period, is dominated by a conflict or independence model that culminates in the secularization of science, where knowledge is based solely on reason and empirical experience, independent of religious authority. This literature review aims to delineate the fundamental ontological and epistemological differences between the two traditions and explore the implications of these different perspectives for the development of civilization and scientific ethics.